Upaya Meningkatkan Hasil Belajar IPAS dengan Pendekatan Culturally Responsive Teaching di Kelas V SDN 101766 Bandar Setia - Matondang, Fatimah Zahra; Harahap, Yulia Sari; Sujarwo, Sujarwo; Nurhafni, Nurhafni; Pakpahan, Naomi (Indo-MathEdu Intellectuals Journal, 2024)
Low student learning outcomes are a major problem in today's education world. This is also felt by SDN 101766 Bandar Setia, an appropriate learning innovation is needed, one of which is by implementing the Culturally Responsive Teaching (CRT) approach. The purpose of this study was to investigate the implementation of the CRT approach in the Project-Based Learning (PJBL) model at SDN 101766 Bandar Setia to improve the learning outcomes of grade V students of SDN 101766 Bandar Setia in the subject of Science on the material of the Human Digestive System. This type of research is classroom action research (CAR) which is carried out in 2 cycles, covering 4 stages, namely: planning, action, observation and, reflection. The data collection techniques used are observation, documentation and tests with qualitative and quantitative data analysis. The results of the study showed that, in cycle I only 77.3% of students achieved learning completion. Then it increased significantly to 91%. Based on these findings, it can be concluded that the CRT approach is effective in improving science learning outcomes on the Human Digestive System material in class V of SDN 101766 Bandar Setia.